2012
DOI: 10.1080/10810730.2011.585696
|View full text |Cite
|
Sign up to set email alerts
|

Social and Psychological Determinants of Levels of Engagement With an Online Breast Cancer Support Group: Posters, Lurkers, and Nonusers

Abstract: Despite the benefits and growing availability of online cancer support groups, many breast cancer patients still do not actively participate in the support groups. To better understand cancer patients’ online information and support seeking behaviors, this study explores how various social and psychological characteristics predict different levels of engagement with an online breast cancer support group: posters, lurkers, and non-users. The study sample included 231 recently diagnosed breast cancer patients. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 28 publications
4
87
1
5
Order By: Relevance
“…These service roles allowed me to watch the development of interesting research findings and theory development in the areas of social support, communication, and health, as well as computermediated communication. As time went on, scholars began to merge theory from both areas in an attempt to make stronger causal claims about the influence of social support network members on specific health outcomes (Han et al, 2012;Liu and Yu, 2013;Oh et al, 2014), by advancing and testing hypotheses stemming from these theoretical frameworks. Numerous extraneous variables and mediating variables have been identified, and they are now being controlled for in much of today's online social networks and health outcomes research.…”
Section: My Research Background In Social Support and Health Outcomesmentioning
confidence: 99%
“…These service roles allowed me to watch the development of interesting research findings and theory development in the areas of social support, communication, and health, as well as computermediated communication. As time went on, scholars began to merge theory from both areas in an attempt to make stronger causal claims about the influence of social support network members on specific health outcomes (Han et al, 2012;Liu and Yu, 2013;Oh et al, 2014), by advancing and testing hypotheses stemming from these theoretical frameworks. Numerous extraneous variables and mediating variables have been identified, and they are now being controlled for in much of today's online social networks and health outcomes research.…”
Section: My Research Background In Social Support and Health Outcomesmentioning
confidence: 99%
“…The forum posts that we included contained for obvious reasons only utterances from patients that are present online. The estimations of percentages of active and non-active online group member differ from 1 to 10% [33], to a quarter active users [13] to about half of the group members [25,34]. It has been found that posters report higher levels of empowerment than lurkers, even though lurkers also benefit from reading the forum texts [13,25,34].…”
Section: Limitationsmentioning
confidence: 99%
“…Some patients are merely lurkers (i.e., people who read social media but do not write posts), while others are active posters [25][26][27]. Because of these differences, the types of messages patients post online might differ, especially when it comes to empowerment.…”
Section: Online Activity and Empowermentmentioning
confidence: 99%
“…Furthermore, some counterintuitive finding in the U.S. study, such that low-income people usually regarded as being underserved for Internet access were more likely to use social media for food recall information, also warrant future study in Korea. It is plausible that some deficits in resources in a face-to-face context were not barriers to active use of social media for food recalls, but they were rather motivators to use a more engaging communication tool (Han et al, 2012). Risk perception (Rimal & Real, 2003) and perceived trustworthiness of the Internet and that of health professionals (Hou & Shim, 2011;Kivits, 2004) also deserve attention as primary predictors of social media use for food risk information in Korea.…”
Section: ) Theoretical Implicationsmentioning
confidence: 99%
“…Based on the CMIS (Johnson, 1997) and supporting evidence in related research(e.g., Carlsson, 2000;Fox & Jones, 2009;Han et al, 2012;Rains, 2007;Tian, Thompson, & Robinson, 2006), the following variables were assessed as the predicting variables.…”
Section: ) Predicting Variablesmentioning
confidence: 99%